A Need Analysis of EFL Learning at Elementary School : A Case Study - Ketut Santi Indriani (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to identify obstacles and analyze needs during the English learning process at SD Negeri 1 Kaba-Kaba, Tabanan, Bali. Learning outcomes for the previous two academic years showed unsatisfactory results. Therefore, this study was conducted to determine the constraints and needs of the learning process in this elementary school. This research is a field research with a qualitative descriptive approach. The data population in this study were 107 students in grades 3-5 and an English teacher. Data were obtained through observation and interviews with 31 students and English teachers. The results of data analysis showed that there were several obstacles faced during the English learning process, namely (i) students who had difficulty concentrating during the learning process, (ii) students' physical condition during the learning process, (iii) active students were found to interfere with the learning process, (iv) lack of supporting facilities and infrastructure to support classroom learning and (v) monotonous teaching methods. In relation to these constraints, several needs in the learning process are (i) good classroom management, (ii) interesting teaching methods, (iii) use of teaching aids in the learning process and (iv) determination of learning outcomes based on the curriculum.